2022
DOI: 10.1155/2022/8091838
|View full text |Cite
|
Sign up to set email alerts
|

Application of Decision Tree in PE Teaching Analysis and Management under the Background of Big Data

Abstract: With the continuous development of physical education reform, the defects and deficiencies of physical education teaching in colleges and universities are increasingly exposed. The reform of the original physical education teaching thought, education system, teaching mode, and method has achieved little. At present, the research on the prediction of physical education teaching achievements is mainly aimed at the prediction of athletes and physical education teaching achievements or the prediction of the past d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Lee et al [11] chose to use decision tree algorithm for business analysis and prediction, because decision tree algorithm is a user-friendly prediction tool, and users can easily interpret data without statistical knowledge or complex formulas.Marynowicz et al [12] used the white-box decision tree model to verify and predict the perceived load rating of players in youth football, examined the relationship between load rating and external measurement of youth football training intensity at the group and individual levels, compared the applicability of the individual model and the group model, and the results showed that,Individual model should be used to evaluate the players to external load response. In addition, the research shows that the decision tree model provides intuitive explanations for the research, bringing the possibility of visualization.Che et al [13] studied physical education under the decision tree under the background of big data, built a physical education management system, used the decision tree model to predict athletes and physical teaching results, and predicted according to the past data of college students, which promoted the continuous deepening of physical education reform. Inspired by the game prediction study of NBA basketball players, we considered whether the correlation between emotional state and game performance inferred from social media posts of professional tennis players could be observed in professional tennis players, and with the same idea in mind, we undertook this project.…”
Section: Predictive Modelmentioning
confidence: 99%
“…Lee et al [11] chose to use decision tree algorithm for business analysis and prediction, because decision tree algorithm is a user-friendly prediction tool, and users can easily interpret data without statistical knowledge or complex formulas.Marynowicz et al [12] used the white-box decision tree model to verify and predict the perceived load rating of players in youth football, examined the relationship between load rating and external measurement of youth football training intensity at the group and individual levels, compared the applicability of the individual model and the group model, and the results showed that,Individual model should be used to evaluate the players to external load response. In addition, the research shows that the decision tree model provides intuitive explanations for the research, bringing the possibility of visualization.Che et al [13] studied physical education under the decision tree under the background of big data, built a physical education management system, used the decision tree model to predict athletes and physical teaching results, and predicted according to the past data of college students, which promoted the continuous deepening of physical education reform. Inspired by the game prediction study of NBA basketball players, we considered whether the correlation between emotional state and game performance inferred from social media posts of professional tennis players could be observed in professional tennis players, and with the same idea in mind, we undertook this project.…”
Section: Predictive Modelmentioning
confidence: 99%
“…The software IBM SPSS modeler was used to create a decision tree model (parameters to be set as follows: the maximum depth of the tree structure is 5, the minimum number of cases of nodes influencing the change in the physical fitness of toddlers is 100, the minimum number of instances of sub-nodes is 50, and the minimum change value of Gini coefficient is 0.0001), and a 10-level crossover was used to verify the accuracy of the model identification. The Chi-squared Automatic Interaction Detector (CHAID), also known as the chi-square automatic interaction detection algorithm, is a decision tree technique based on adjusted significance testing (Bonferroni test), uses the chi-squared test to evaluate the significance of variable grouping on the target variable and selects the splitting point that maximizes the chi-squared value as the optimal splitting point (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Due to the characteristics of large sample size, multiple indicators, this study used the significance of chi-square tests to automatically determine the grouping variables and split values of the multivariate contingency table, thereby quickly and effectively identifying the main influencing factors.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…as these methods lack deep data mining and decision analysis and are vulnerable to covariance problems (21,22). In recent years, scholars have used decision trees in data mining techniques to conduct functional explorations in many fields (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). As an important classification technique in data mining, decision trees are capable of effectively identifying the main influencing factors of physical changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, physical fitness training in schools is still based on traditional methods, with problems such as unscientific training methods, unprofessional training teams, unsystematic training plans, inaccurate training monitoring, advanced training methods, and ineffective training management, leading to low training efficiency and poor effectiveness, high incidence of injuries and illnesses, and serious impact on the generation of combat effectiveness [4]. With the rapid development of science and technology, using intelligent methods to solve the problems existing in physical training has become a future trend, which has great potential for improving the level of military physical training.…”
Section: Introductionmentioning
confidence: 99%